The gratitude training to enhance the psychological well-being among adolescents with single parents - Nuriah Halleyda; Muhammad Japar (Humanitas: Indonesian Psychological Journal, 2023)
Psychological well-being is an important component for adolescents. This research examined the influence of gratitude training to enhance the psychological well-being of adolescents with single parents at a Junior High School. This research applied a true experimental method with a pretest-posttest control group design. The subjects were taken randomly and consisted of 24 adolescents with single parents. The subjects were then grouped into experimental and control groups, each consisting of 12 individuals. The experimental group received the gratitude training, consisting of 6 sessions. The psychological well-being scale for Indonesian adolescents aged between 12 and 15 was used to collect the data. ANOVA mixed design with SPSS 25 for Windows was applied to analyze the data. The result shows a significant interaction between the group and test, indicating the changes between the experiment and control groups significantly differ from pretest to posttest. Based on post hoc analysis, there is a significant mean difference in psychological well-being in the experimental group, with the mean of the pretest being lower than in the posttest. Therefore, gratitude training enhances the psychological well-being of adolescents with single parents. Adolescents need to apply gratitude to their daily activities to enhance their psychological well-being.